2009
DOI: 10.1071/fp09117
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterisation of aquaporins in the grapevine, Vitis vinifera

Abstract: Abstract. Plant aquaporins belong to a large superfamily of conserved proteins called the major intrinsic proteins (MIPs).There is limited information about the diversity of MIPs in grapevine, and their water transport capacity. The aim of the present study was to identify MIPs from grapevine and functionally characterise water transport of a subset of MIPs. Candidate genes were identified, by screening a Vitis vinifera L. (cv. Cabernet Sauvignon) cDNA library with gene specific probes, for aquaporin cDNAs enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 78 publications
4
86
1
3
Order By: Relevance
“…induced a 54-fold increase in membrane P f , a value comparable to those detected when using this experimental system for plant aquaporins (Marjanović et al, 2005;Secchi et al, 2007) and to those reported for the four grapevine PIP2 aquaporins analyzed by Shelden et al (2009). Taken together, these results suggest that VvPIP2;4N is a water-transporting aquaporin that may potentially offer a remarkable contribution to water transcellular transport in grape tissues.…”
Section: Effects Of Vvpip2;4n Overexpression On Hydraulic Conductivitsupporting
confidence: 69%
See 4 more Smart Citations
“…induced a 54-fold increase in membrane P f , a value comparable to those detected when using this experimental system for plant aquaporins (Marjanović et al, 2005;Secchi et al, 2007) and to those reported for the four grapevine PIP2 aquaporins analyzed by Shelden et al (2009). Taken together, these results suggest that VvPIP2;4N is a water-transporting aquaporin that may potentially offer a remarkable contribution to water transcellular transport in grape tissues.…”
Section: Effects Of Vvpip2;4n Overexpression On Hydraulic Conductivitsupporting
confidence: 69%
“…3A). These results are in contrast with the very low expression levels of VvPIP2;4 in roots reported by Vandeleur et al (2009); however, no correspondence was observed between the primers used by those authors and those used in this study, confirming that VvPIP2;4N is different from VvPIP2;4 described by Shelden et al (2009) and Vandeleur et al (2009). The expression pattern of VvPIP2;4N suggests that this aquaporin could be a specific root isoform, probably involved in the regulation of root hydraulic conductance.…”
Section: Functional Characterization Of Vvpip2;4ncontrasting
confidence: 56%
See 3 more Smart Citations